Judicial vetoes : decision-making on mixed selection constitutional courts - Tiede, Lydia Brashear, 1965- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
How does the selection of judges influence the work they do in important constitutional courts? Does mixed judicial selection, which allows more players to choose judges, result in a court that is more independent and one that can check powerful executives and legislators? Existing literature on constitutional courts tends to focus on how judicial behaviour is motivated by judges' political preferences. Lydia Brashear Tiede argues for a new approach, showing that, under mixed selection, institutions choose different types of judges who represent different approaches to constitutional adjudication and thus have different propensities for striking down laws. Using empirical evidence from the constitutional courts of Chile and Colombia, this book develops a framework for understanding the factors, external and internal to courts, which lead individual judges, as well as the courts in which they work, to veto a law.
Introduction -- The implications of mixed judicial selection on decision-making -- Mixed judicial selection : prevalence and variation -- The Chilean Constitutional Tribunal in political context -- The Colombian Constitutional Court in political context -- Determinants of legal invalidation by constitutional judges -- Determinants of legal invalidation by constitutional courts -- Weak judicial vetoes and contentious politics -- Conclusion : judicial selection and decision-making.
Title from publisher's bibliographic system (viewed on 25 Jul 2022).
Keywords: Chile. -- Tribunal Constitucional -- Decision making; Colombia. -- Corte Constitucional -- Decision making; Constitutional courts -- Chile -- Decision making; Political questions and judicial power -- Chile; Constitutional courts -- Colombia -- Decision making; Political questions and judicial power -- Colombia